PENGARUH PAMERAN DAN DESAIN KEMASAN TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Produk NA CoffeeKondisi Khusus 2009 Pasca dikembangkan BRR NAD-Nias) - Teuku Roli Ilhamsyah Putra (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2014)
Exhibition and package design are two marketing programs which must be considered in a product development. Efficacy of product development is measured through consumer interest to product that bearing purchasing decision. This matter could be provable from measurement result by using model of regression, model of sensitivity and model of effectiveness. The purpose of this research is to know the influence of exhibition and package design on purchasing decision by using primary and secondary data.This research has a cross sectional data that collected in 2009, when Badan Rehabilitasi dan Rekonstruksi NAD Nias programs for seriously developing NA Coffee had already done and this research solution depictsthe condition in that interesting era.The Result of research indicates that for totally, activity of exhibition and package design have significantly effect to consumer interest behaviour to NA Coffee (Adjusted R Square = 0,657, F test 17,546 is bigger than F table 3,07 at level of significant 5 %). Partially, exhibition activity effects positive and significant (b1 = 0,188, significant 0,000). In the same way, package design also have a positive significant impact (b2 = 0,245, significant 0,001). Both of program give a positive response to consumer interest tend to buy NA Coffee. Others, in effectiveness, exhibition and package are very effective to increase earnings of NA Coffee (Income Indicator equals to 2,159, meaning that the real advantage is increasing amount 215,9 % after the exhibition and package design program have been implemented.Result of research recommends NA Coffee should continue the promotion program more intensively. This issue is evidenced from the fact of increasing of sales is caused by promotion activity through exhibitions during year 2008, whereby previously the producer only did the communication activity from word to mouth. On the other hand, the packaging of product should be able to adapted to the consumer requirements, for example the case of product volume and packaging material should be fulfill the consumer’s needs and logistic issues. All the subjects are aimed for product to have a character of flexible, attractive and protect the content of product itself.